Magnetospheric-density estimation from SuperDARN VLOS data to identify magnetospheric regions, by using FLR events in ionospheric or ground/sea backscatters - Kawano, Hideaki; Yukimatu, Akira; Nishitani, Nozomu; Tanaka, Yoshimasa; Saita, Satoko; Hori, Tomoaki (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OS] Space and upper atmospheric sciences, Wed. 15 Nov. / Entrance Hall (1st floor), National Institute of Polar Research conference object